THE EFFECTIVENESS OF GIVING GINGER HOT DRINKS TO REDUCE NAUSEA AND VOMITING COMPLAINTS IN PREGNANT WOMEN: LITERATURE REVIEW - Faisal Akbar; Rika Ayunniawati; Asma Fida Ulya (UNEJ e-Proceeding, 2022)
Along with nausea and vomiting, pregnant women enjoy mental, physical, and hormonal changes that lead to many processes, can lead to tissue damage and thus may impair maternal health and fetal development.Initial treatment of pregnancy vomiting may include supplements such as emotional counseling, dietary changes, and administration of ginger wedang. Treatment should be included. The motivation for this literature review is to discover the efficacy of giving ginger wedang to reduce forensic cases of nausea and vomiting in pregnant women. We utilized a literature review that used the keywords 'Ginger (AND) Nausea Vomiting (AND) Pregnancy' and searched for journal articles from 2018 to 2022 using the keyword Schooler. The words "ginger nausea vomiting pregnant". Results from 10 journal articles using a systematic review approach were 1 journal article, 2 randomized controlled trials modified into journal articles, and 7 journal articles. Results from all articles reviewed indicate that a total dose of 250 mg of ginger was taken orally for 4 days for the treatment of ginger wedan when ingested by pregnant girls with complaints of nausea and vomiting. 0.05 is effective. Based on the results of the literature review, it is hoped that this network will realize her Wedang Ginger intervention for pregnant girls complaining of nausea and vomiting and will inform similar studies. Background: Pregnant women will experience psychological, physical, and hormonal changes that cause many complaints, such as nausea and vomiting. Emesis gravidarum if ignored will continue to become hyperemesis gravidarum and if left unchecked can cause tissue damage, so that it can endanger the health of pregnant women and the development of the fetus. Initial therapy in emesis gravidarum should include emotional support, dietary changes, and complementary therapies such as giving ginger wedang Purpose: Analyzing the effectiveness of giving ginger wedang to decrease complaints of nausea and vomiting in pregnant women. Methods: This study uses a Literature Review with a search for journal articles in 2018 to 2022 conducted on the PubMed and Taylor & Francis databases with the keyword "Ginger (AND) Nausea Vomiting (AND) Pregnancy" and Scholar with the keyword "Ginger Nausea Vomiting Pregnant Women". The results obtained were 10 journal articles according to the inclusion criteria using the Systematic Review method of 1 journal article, 2 journal articles Randomized Controlled Trial, and 7 journal articles Quasi-experimental studies. Results: The results of all the articles that have been reviewed show that the administration of ginger wedang is effective for consumption by pregnant women with complaints of nausea and vomiting with a dose of ginger as much as 250 mg within 4 days ​